Explorando a cartografia: um estudo sobre as ocupações secundaristas - Pacheco, Carolina Simões (Diálogos Latinoamericanos, 2022)
Most research in the social sciences assumes a qualitative character when dealing with the theme of social movements. Aiming to contribute to the development of quantitative research and to promote interdisciplinarity, we developed a cartographic project of high school occupations that occurred in Paraná in 2016. To achieve this, we situate the student movement as a youth movement and describe the political action of Brazilian high school students. We then verify the list of occupied schools and developed maps of the numbers of occupations. We observe the concentration of occupations in the largest municipalities of the state and, simultaneously, the decentralized character of the movement. Finally, we adopt the methodology proposed by IBGE, which divides the states into Intermediate Geographic Regions. In this context, this division has proved to be efficient for the sociospatial understanding of occupations and can be applied to the analysis of contestatory movements.